Generation of a novel CD30+ B cell subset producing GM‐CSF and its possible link to the pathogenesis of systemic sclerosis. (14th July 2020) - Higashioka, K.; Kikushige, Y.; Ayano, M.; Kimoto, Y.; Mitoma, H.; Kikukawa, M.; Akahoshi, M.; Arinobu, Y.; Horiuchi, T.; Akashi, K.; Niiro, H.
Summary: Systemic sclerosis (SSc) is a T helper type 2 (Th2)‐associated autoimmune disease characterized by vasculopathy and fibrosis. Efficacy of B cell depletion therapy underscores antibody‐independent functions of B cells in SSc. A recent study showed that the Th2 cytokine interleukin (IL)‐4 induces granulocyte–macrophage colony‐stimulating factor (GM‐CSF)‐producing effector B cells (GM‐Beffs ) in humans. In this study, we sought to elucidate the generation mechanism of GM‐Beffs and also determine a role of this subset in SSc. Among Th‐associated cytokines, IL‐4 most significantly facilitated the generation of GM‐Beffs within memory B cells in healthy controls (HCs). In addition, the profibrotic cytokine transforming growth factor (TGF)‐β further potentiated IL‐4‐ and IL‐13‐induced GM‐Beffs . Of note, tofacitinib, a Janus kinase (JAK) inhibitor, inhibited the expression of GM‐CSF mRNA and protein in memory B cells induced by IL‐4, but not by TGF‐β. GM‐Beffs were enriched within CD20 + CD30 + CD38 −/low cells, a distinct population from plasmablasts, suggesting that GM‐Beffs exert antibody‐independent functions. GM‐Beffs were also enriched in a CD30 + fraction of freshly isolated B cells. GM‐Beffs generated under Th2 conditions facilitated the differentiation from CD14 + monocytes to DC‐SIGN + CD1a + CD14 − CD86 + cells, which significantly promoted the proliferation of naive T cells. CD30 + GM‐Beffs were more pronounced in patients with SSc than in HCs. A subpopulation of SSc patients with the diffuse type and concomitant interstitial lung disease exhibited high numbers of GM‐Beffs . Together, these findings suggest that human GM‐Beffs are enriched in a CD30 + B cell subset and play a role in the pathogenesis of SSc. Abstract : Systemic sclerosis (SSc) is a Th2‐associated fibroinflammatory autoimmune disease, in which B cells are suggested to exert antibody‐independent functions. We found that CD30+GM‐CSF‐producing B cells (GM‐Beffs) were generated from memory B cells by Th2 cytokines along with TGF‐β and induced differentiation to monocyte‐derived dendritic cells. CD30+GM‐Beffs were increased in SSc patients with the diffuse type and concomitant ILD, suggesting their pivotal role in disease pathogenesis.